2001
DOI: 10.1080/136518201753242208
|View full text |Cite
|
Sign up to set email alerts
|

Quality control in laparoscopic cholecystectomy: operation notes, video or photo print?

Abstract: Operation notes,video and photo print are complementary, and the combination records CVS conclusively in nearly every case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 8 publications
0
21
0
1
Order By: Relevance
“…For legal and teaching goals, guidelines of the Dutch Association for Surgery advise storing the images of CVS. Since the introduction of CVS, only one study has been performed to determine the most reliable method for recording CVS [13]. Plaisier et al [13] presented a study in 2001, stating that video was superior to photo print with regard to quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For legal and teaching goals, guidelines of the Dutch Association for Surgery advise storing the images of CVS. Since the introduction of CVS, only one study has been performed to determine the most reliable method for recording CVS [13]. Plaisier et al [13] presented a study in 2001, stating that video was superior to photo print with regard to quality.…”
Section: Discussionmentioning
confidence: 99%
“…Since the introduction of CVS, only one study has been performed to determine the most reliable method for recording CVS [13]. Plaisier et al [13] presented a study in 2001, stating that video was superior to photo print with regard to quality. However, when a good quality of photo print was achieved, photo print recorded CVS more conclusively than video.…”
Section: Discussionmentioning
confidence: 99%
“…Confirmation of CVS may be in the surgeon's own mind or the surgeon may point it out in a “time out”, which is an appropriate step in a teaching situation. Also, there is an opportunity to record the CVS in still photos or by videotapes .…”
Section: Step 1 Getting Secure Anatomical Identification Whenever Comentioning
confidence: 99%
“…These could then be randomly audited for quality control purposes. Comments from the two observers highlighted that the photo quality affected the scoring for some patients and previous studies have suggested that taking a short video may provide a more accurate documentation of the CVS …”
Section: Discussionmentioning
confidence: 99%